Utilization pattern of Haemophilus influenza type b vaccine in eight provinces of China. Issue 4 (3rd April 2018) - Li, Yan; Yue, Chenyan; Wang, Yamin; Zhu, Xu; Martin, Kathryn; Scherpbier, Robert W.; Liu, Jiechen; Wang, Zhiguo; Ma, Yujie; Cheng, Huijian; Zhang, Zhenguo; Wang, Qing; et al.
ABSTRACT: Objective: In China, Hib vaccine is a private-sector vaccine that is an option for parents to select to give to their children; it must be paid for out-of-pocket because it is not included in the government's Expanded Program on Immunization (EPI). We evaluated utilization patterns of Hib vaccine to provide evidence in support of development of a national Hib vaccination strategy. Methods: We obtained lists of children from immunization information systems (IIS) of counties or districts in 8 provinces of China. Using these lists, we selected 10 children at random from each birth cohort from 2008 through 2012. We obtained Hib vaccination dates from official vaccination certificates. The target sample size was 1, 000 children. Results: We were able to obtain records for 978 subjects of the selected subjects; of these, 44.79% had received at least 1 dose of Hib vaccine, and 15.54%, 5.83%, 12.27%, and 11.15% had received one, two, three, and four doses, respectively. Per capita GDP was positively correlated with receipt of at least one dose of Hib vaccine. Among the 438 subjects who received Hib vaccine, 27% received 1 dose after 12 months of age; 15%, 7%, and 23% received one of three other patterns of Hib vaccination recommended by the World Health Organization (WHO) [a 3-dose primary series; 2 primary series doses and 1 booster; or 3 primary series doses and 1 booster]. The other 28% of subjects received patterns of Hib vaccination not recommended by WHO. Considering protection from Hib disease as receipt of a WHO-recommended Hib vaccine schedule, 29% of subjects could be considered protected after 12 months of age, 52% could be considered protected during infancy and beyond, and 19% could be considered to not have been protected adequately, despite being vaccinated. Conclusions: Coverage with Hib vaccine was low. There were significant differences between WHO recommendations and actual patterns of use of Hib vaccine, with half of vaccine recipients receiving no protection during infancy and one fifth receiving non-protective Hib vaccination patterns. Inclusion of Hib vaccine into China's EPI system, which provides vaccine at no charge to parents and makes specific vaccination schedule standards, has potential to make more effective use of Hib vaccine.